Effect of thermal and non-thermal treatment on the quality of honey: a review - Mohd Fauzi, Noor Akhmazillah; Lee, Andy Chyi Wei; Razali, Muhammad Faiz (Penerbit UTHM, 2017)
In recent year, there has been an increasing amount of studies on the quality of honey particularly physicochemical properties and its nutritional value. Unfortunately, these properties will be affected when it is exposed to a temperature higher than 60°C during the conventional thermal processing and also altered its nutritional properties such as antioxidant activity and brown pigment formation. Hence, non-thermal processing that might be proven to be significant benefit, applied without causing significant heating that can damage taste, texture and nutritional value of honey. Although there are many research has been done on non-thermal processing on the bio-compounds in various foods in various foods, the application of non-thermal processing for the enhancement of the quality of honey is underexplored. By studying the effects of non-thermal processing on the quality of honey, it will help to improve the use of honey and also a diversification in food products containing it.